2009
DOI: 10.1182/blood-2009-02-207134
|View full text |Cite
|
Sign up to set email alerts
|

Role of tyrosine phosphatase SHP-1 in the mechanism of endorepellin angiostatic activity

Abstract: Endorepellin, the C-terminal domain of perlecan, is a powerful angiogenesis inhibitor. To dissect the mechanism of endorepellin-mediated endothelial silencing, we used an antibody array against multiple tyrosine kinase receptors. Endorepellin caused a widespread reduction in phosphorylation of key receptors involved in angiogenesis and a concurrent increase in phosphatase activity in endothelial cells and tumor xenografts. These effects were efficiently hampered by function-blocking antibodies against integrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(77 citation statements)
references
References 51 publications
2
75
0
Order By: Relevance
“…We hypothesized that this could occur if DV binds to α5β1 differently from fibronectin, as has been demonstrated for DV and collagen I binding to α2β1 integrin (27,31). Supplemental Figure 9 demonstrates that soluble, but not insoluble, DV is capable of increasing brain endothelial proliferation, even in the presence of fibronectin, a scenario that mimics the post-stroke fibronectin-rich in vivo environment.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…We hypothesized that this could occur if DV binds to α5β1 differently from fibronectin, as has been demonstrated for DV and collagen I binding to α2β1 integrin (27,31). Supplemental Figure 9 demonstrates that soluble, but not insoluble, DV is capable of increasing brain endothelial proliferation, even in the presence of fibronectin, a scenario that mimics the post-stroke fibronectin-rich in vivo environment.…”
Section: Discussionmentioning
confidence: 85%
“…It was next hypothesized that DV could be neuroprotective and restore post-stroke motor function after ischemic stroke by increasing growth factor concentrations. We focused on VEGF for several reasons: DV activity outside of the brain has been linked to the suppression of VEGF signaling (27), perlecan synthesis and release in brain endothelial cells is induced by VEGF (28), and VEGF is known to be neuroprotective (8,9). We found that total VEGF concentrations following post-stroke DV treatment (as compared with PBS treatment)…”
Section: Resultsmentioning
confidence: 99%
“…Like other mentioned angiogenesis inhibitors, such as arresten, canstatin, endostatin, and tumstatin, endorepellin mediates its antiangiogenesis functions through binding to ␣2␤1-integrin, a key angiogenesis receptor (376). This interaction disintegrates the actin cytoskeleton and focal adhesions (237). The laminin-like globular domain (LG3) of endorepellin can be released by further proteolytic processing with BMP-1 (111).…”
Section: Posttranslationally Modified Proteins Affect Cell Phenotype:mentioning
confidence: 99%
“…Endorepellin blocks endothelial cell migration and capillary morphogenesis, both in vitro and in vivo [26]. Endorepellin interacts specifically with the α2β1 integrin [27], and stimulation with endorepellin induces the interaction and phosphorylation of Src homology-2 protein phosphatase-1 with integrin α2 in endothelial cells [28]. Endorepellin LG3 fragment (amino acids 3687-4391) has potent antiangiogenic properties [29].…”
Section: Discussionmentioning
confidence: 99%